Effect of increased and maintained frequency of speed endurance training on performance and muscle adaptations in runners - Skovgaard, C.; Winfield Almquist, N.; Bangsbo, J. (Journal of Applied Physiology, 2017)
The aim of the study was, in runners accustomed to speed endurance training (SET), to examine the effect of increased and maintained frequency of SET on performance and muscular adaptations. After familiarization (FAM) to SET, 18 male (n = 14) and female (n = 4) runners (VO2max: 57.3 ± 3.4 ml/min; means ± SD) completed 20 sessions of maintained low-frequency (LF; every fourth day; n = 7) or high-frequency (HF; every second day; n = 11) SET. Before FAM as well as before and after an intervention period (INT), subjects completed a series of running tests and a biopsy from m. vastus lateralis was collected. Ten-kilometer performance improved (P < 0.05) ~3.5% during FAM with no further change during INT. Time to exhaustion at 90% vVO2max was 15 and 22% longer (P < 0.05) during FAM and a further 12 and 16% longer (P < 0.05) during INT in HF and LF, respectively. During FAM, muscle expression of NHE1 and maximal activity of citrate synthase (CS) and phosphofructokinase (PFK) increased (P < 0.05), running economy (RE) improved (P < 0.05), and VO2max was unchanged. During INT, both HF and LF increased (P < 0.05) muscle expression of NKAß1, whereas maximal activity of CS and PFK, RE, and VO2max were unchanged. Furthermore, during INT, muscle expression of FXYD1 and SERCA1, and FXYD1 activity increased (P < 0.05) in HF, while muscle expression of SERCA2 decreased (P < 0.05) in LF. Thus increased or maintained frequency of SET leads to further improvements in short-term exercise capacity, but not in 10-km running performance. The better short-term exercise capacity may be associated with elevated expression of muscle proteins related to Na+/K+ transportation and Ca2+ reuptake.